Model for calculation of penetration resistance from easily measurable soil physical properties - MAITY, P; AGGARWAL, P; DEY, P (The Indian Journal of Agricultural Sciences, 2013)
Higher cost of equipment and requirement of trained human power often limit the direct measurement of soil penetrationresistance (PR) in developing countries. Hence, in this paper, we present an indirect measurement of PR from easilymeasurable soil physical properties in surface (0-15 cm) and subsurface (15-30 cm) layer. Experiments conducted on 12hectare area of IARI main farm under two texturally different soils, viz sandy loam and loam showed highly significantdifferences in the values of PR, soil water content (SWC) and bulk density (BD) both before and after ploughing. Althoughthe average PR and BD values of 15-30 cm layer were reduced after ploughing, they remained above critical limits which confirmed the presence of permanent plough pan between 15-30 cm. The BD registered a significant positive correlation to PR, while SWC followed a significant negative correlation. Stepwise regression analysis of PR, BD and SWC of both soils showed that among all soil physical parameters, SWC exerted maximum influence on PR both before and after ploughing. While SWC alone contributed up to 40-65% variation in PR, it accounted for 60-80% of variations in combination with BD. However, addition of clay (%) and sand (%) in the regression model did not improve the coefficient ofdetermination. The study conclusively proved that the researchers have yet another tool and dimension to use SWC, BD, clay (%) and sand (%) as an index for calculation of PR value.